Psychometric Properties of the Urdu Version of Diabetes Knowledge Questionnaire - Bukhsh, Allah; Wen, Shaun Huey Lee; Pusparajah, Priyia; Hayat Khan, Amer; Mehmood Khan, Tahir (Frontiers Media, 2017)
Objective: Patient education is a key element in the treatment of diabetes. Assessment of diabetes knowledge is important for optimum treatment. For the assessment of diabetes knowledge, validated tool is essential. None of such validated tool is available in Urdu language. Therefore, the aim of this study was to translate and examine the psychometric properties of the 24-item Urdu version of Diabetes Knowledge Questionnaire (DKQ) among type 2 diabetes patients. Methods: Standard “forward–backward” process was used to translate DKQ into Urdu language. Later, it was validated on a convenience sample of 130 patients with type 2 diabetes, between July and September 2016. Internal consistency was assessed by reliability analysis, one-way analysis of variance was applied for known group validity and multivariate linear logistic regression was applied for identifying significant predictors for patients’ DKQ score. results: Good internal consistency was observed for DKQ (Cronbach’s α = 0.702). The mean HbA1c of the patients was 8.55% (±1.91). DKQ scores of patients’ with “good glycemic control” (14.22 ± 2.4) were observed significantly higher (P < 0.05) than patients with “poor glycemic control” (12.56 ± 2.75). Multiple linear regression revealed that patients’ HbA1c (OR −0.17, CI −1.111, −0.023) and patients’ education (OR 0.17, CI −0.032, 0.758) were significant predictors for DKQ sum score. conclusion: Urdu version of the DKQ is a valid and reliable instrument for adequate estimation of disease knowledge and its association with glycemic control in type 2 diabetes patients in Pakistan.